Study the effect of Lysostaphin, on methicillin resistant Staphylococcus aureus( MRSA) biofilm formation - AL-Sheikh, Elaf; Yosif, Hana (Iraqi Journal of Science, 2023)
This study included collection of 100 specimens from patients in AL-Kindy Teaching Hospital and teaching laboratories of Medical City Hospitals in Baghdad during the period from August to December 2012 ,these specimens differed in their sources which included 19 nasal swab, 16 wound swab,27 burn swab, 7 pus, 15 sputum, 10 corneal swab and 6 urine . Only 38 (38%) isolates was identified as Staphylococcus. In this study, 29 isolates (76.3%) were coagulase-positive (COPS), while only 9 isolates(23.6%) were coagulase negative (CONS), from total 38 isolates of Staphylococci.The distribution of Methicillin resistance among Staphylococcus spp. was investigated by disc diffusion method. In this study, 21 isolates (55.26%) showed resistant to the Methicillin while 17 isolates (44.73%) were sensitive.The ability to produce slime layer by MRSA isolates was also investigated and the results showed that all isolates of MRSA was produced slime layer when tested by tube method, but the amounts of adherent materials were differ among the isolates. However, the results by Congo red agar method showed that 57% of MRSA isolates produced strong slime layer and 43% of MRSA obtained negative result. Similarly the ability of MRSA to produce biofilm by tissue culture plate (TCP) was investigated and the results indicated that MRSA isolates showed highly and strong biofilm formation, and the OD value of biofilm formation ranged between 0.262 - 0.311. Additionally the OD value of biofilm formation significantly increased in addition of 1% glucose to the media.Statistical analysis showed slightly effect of lysostaphin under (5.625μg/ml MIC) on biofilm formation ability of (MRSA S3) optical density was reduced to (0.312 nm) in comparable with control group (0.389nm).